Moderate nutrient restriction of beef heifers alters expression of genes associated with tissue metabolism, accretion, and function in fetal liver, muscle, and cerebrum by day 50 of gestation() - Crouse, Matthew S (Transl Anim Sci, 2019)
We hypothesized that a moderate maternal nutrient restriction during the first 50 d of gestation in beef heifers would affect transcript abundance of genes associated with tissue metabolism, accretion, and function in fetal liver, muscle, and cerebrum. Angus-cross heifers were estrus synchronized and assigned at breeding to one of two dietary treatments (CON- 100% of nutrient requirements to gain 0.45 kg/d; RES- 60% of CON). At day 50 of gestation, 14 heifers were ovariohysterectomized, and fetal liver, muscle, and cerebrum were collected. Transcriptome analysis via RNA-seq was conducted on the Illumina HiSeq 2500 platform using 50-bp paired-end reads at a depth of 2 × 10.4M reads/sample. Bioinformatic analysis was performed using the Tuxedo Suite and ontological analysis with DAVID 6.8. For fetal liver, muscle, and cerebrum, a total of 548, 317, and 151 genes, respectively (P < 0.01) were differentially expressed, of which 201, 144, and 28 genes, respectively were false discovery rate protected (FDR; q < 0.10). Differentially expressed genes were screened for fit into functional categories of pathways or ontologies associated with known impacts on tissue metabolism, accretion, and function. In fetal liver, five functional categories of interest (n = 125 genes) were affected by nutritional treatment: metabolic pathways, protein kinase, nucleosome core, mRNA splicing, and complement/coagulation cascades, of which 105 genes were upregulated in RES. In fetal muscle, three functional categories of interest (n = 106 genes) were affected by nutritional treatment: skeletal muscle, embryogenesis, and signaling cascades, of which 64 genes were upregulated in RES. In fetal cerebrum, three functional categories of interest (n = 60 genes) were affected by nutritional treatment: hippocampus and neurogenesis, metal-binding, and cytoskeleton, of which 58 genes were upregulated in RES. These results demonstrate that a moderate maternal nutrient restriction during the first 50 d of gestation in beef heifers alters transcript abundance of genes potentially impacting tissue metabolism, accretion, and function in fetal liver, muscle, and cerebrum. Furthermore, these results indicate that affected categories are tissue-specific and moderate maternal nutrient restriction generally increases expression of genes in fetuses from RES fed dams. Finally, these data lay the foundation upon which further research that identifies phenotypic responses to changes in these pathways may be elucidated.